2013
DOI: 10.1088/0957-4484/24/11/115708
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of graphene sheets in wax composites for electromagnetic interference shielding improvement

Abstract: Rapid advancements in carbon-based fillers have enabled a new and more promising platform in the development of electromagnetic attenuation composites. Alignment of fillers in composites with specific structures and morphologies has been widely pursued to achieve high performance based on taking advantage of unique filler characteristics. In this work, few-layer graphene (FLG), obtained from direct exfoliation of graphite, was fabricated into paraffin wax to prepare FLG/wax composites and investigate their ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…According to the optimized absorption properties, the reflection loss at 14 GHz is good enough and the difference between the pyramid and multilayer design is great. The normalized power loss distribution of the optimized absorbers at 14 GHz were plotted to analyze the enhanced absorption properties of patterned absorbers.…”
Section: Artificial Pattern Designmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the optimized absorption properties, the reflection loss at 14 GHz is good enough and the difference between the pyramid and multilayer design is great. The normalized power loss distribution of the optimized absorbers at 14 GHz were plotted to analyze the enhanced absorption properties of patterned absorbers.…”
Section: Artificial Pattern Designmentioning
confidence: 99%
“…In particular, carbon materials including carbon fibers, carbon nanotubes, and graphene have been widely explored for fabricating lightweight fillers that are effective in microwave absorption composites, with receiving the greatest attention among recent electromagnetic sensitive materials. [13][14][15][16][17][18][19] In the recent study on the carbonbased hybrid fillers, carbon nanotube and graphene nanostructures, mostly reduced graphene oxide (RGO), are more attractive because the sp2 hybridized carbon structure not only provides effective pathways for electromagnetic energy loss, but offers the active site for chemically bonding heterostructures or hetero-atoms in tuning electromagnetic parameters. [20][21][22] In typical examples, Bai and co-workers used polyethylene oxide as the both dispersion agents and matrices in the fabrication of polymeric RGO composites, which show a strong absorption peak around À38.8 dB and an effective absorption bandwidth (the bandwidth with absorption intensity <À10 dB) from 14 to 18 GHz in the investigation range.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Song et al [83] also demonstrated that electric conductive interconnections can be much established more easily for the post-alignment composites at the same graphene loading for the simple reason that the alignment may offer more opportunities for graphene to form conducting interconnections and enhance the absorption contribution of electromagnetic waves. Specifically, few-layered graphene (FLG) may increase the reflection contribution by enlarging the in-plane effective reflection regions of graphene.…”
Section: Aspect Ratio and Orientation Of Graphenementioning
confidence: 96%
“…Hexgonal Ni nanocrystals decorated monolayer graphene [47], polycrystalline Fe 3 O 4 nanoparticles decked r-GO/FLG [48][49][50], and submicron sized CoFe 2 O 4 hollow spheres decorated on single sheet r-GO [51] filled wax composites showed an excellent MA capacity (RL less than −10 dB corresponding to 90 % MA for different thicknesses of the wax composite samples). These composites have shown far superior microwave absorption capacity than the typical nonmagnetic r-GO/FLG particles filled wax composites [52,53].…”
Section: Graphene/wax Compositesmentioning
confidence: 99%